The effect of business regulations on nascent and actual entrepreneurship - André J. van Stel; David J. Storey; A. Roy Thurik (Max Planck Institute of Economics, 2006)
This paper investigates the effect of business regulations on various measures of entrepreneurship. Using data for a sample of countries participating in the Global Entrepreneurship Monitor between 2002 and 2005, we estimate a two-equation model explaining the nascent and the actual entrepreneurship rate, while taking into account the interrelationship between the two variables. Various determinants of entrepreneurship reflecting the demand and supply side of entrepreneurship as well as business regulation measures are incorporated in the model. Data on various categories of business regulations are taken from the World Bank Doing Business data base. Our estimation results suggest that, while entry regulations only have a small and indirect impact on the actual entrepreneurship rate, the impact of labour market regulations is more important. We also find that the determinants of opportunity and necessity entrepreneur-ship are fundamentally different.
Keywords: K20; L51; M13; O57; 330; nascent entrepreneurship; young businesses; business regulations; Global Entrepreneurship Monitor; World Bank Doing Business